Effectiveness of Using Audio Media in Improving Memorizing Short Surahs of the al-Quran - Podungge , Mariaty; Hidayah, Annisa Imanul; Pratama, Apriliyanus Rakhmadi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This study examines the effectiveness of using audio media in improving the memorization of short surahs. This research employs a qualitative descriptive approach with data collection methods including observation, interviews, and documentation. The data sources consist of Islamic Education teachers, classroom teachers, and 33 students. Data analysis techniques were conducted through (1) data reduction, (2) data presentation, and (3) conclusion drawing. Data validity was checked through four steps: 1) Credibility, 2) Dependability, 3) Confirmability, and 4) Triangulation. The results show that the effectiveness of using audio media in improving the memorization of short surahs at Madrasah Tsanawiyah An-Nur Monano Gorontalo is significant. Teachers were able to provide good short surah memorization materials to students, enabling them to memorize the surahs perfectly and fluently. Additionally, teachers were able to impart the understanding to students that memorizing short surahs is beneficial. Besides the fact that many students liked the media, they felt helped in repeatedly reviewing the memorized short surahs fluently and correctly. Thus, audio media is considered effective in facilitating the memorization of short surahs, with a high degree of effectiveness, as evidenced by the following grades: A- 36.36%, B+ 54.54%, C 3.03%, and 6.06%.